Evaluation Of Knowledge and Self Care Practices in Diabetic Patients and Their Role in Disease Management - Padma, Karam; Bele, Samir D; Bodhare, Trupti N; Valsangkar, Sameer (National Journal of Community Medicine, 2012)
Background: Poor awareness and practices among diabetic patients are some of the important variables influencing the progression of diabetes and its complications, which are largely preventable through education and involvement of the patient. Methods: A hospital based cross sectional study was conducted among type 2 diabetics attending diabetes clinic in tertiary care hospital. Knowledge and self care practices were evaluated using a semi structured questionnaire. Statistical methods used included frequencies, proportions and chi square test. Results: A total of 117 diabetic patients consented and participated in the study of whom 63 (53.85%) were male and 54 (46. 15%) female. Majority of the respondents (45.30%) between the age of 41-50 years,75 (64.10 %) belonged to lower class, and 60 (51.28 %) had a duration of disease between 1 to 5 years. 71 (61.68%) were aware of importance of exercise for the control of disease while 88 (75.21%) said that modification in diet is essential for the control of the disease. 75 (64%) of the respondents had achieved glycemic control. Among self care practices, following a controlled diet (p = 0.04), regular exercise (p = 0.04) and compliance with drugs (p = 0.03) were significantly associated with the achieving glycemic control. Conclusion: As evidenced by the study, patients who were regularly involved in self care practices have achieved better glycemic control.